Streptococcus pneumoniae Supragenome Hybridization Arrays for Profiling of Genetic Content and Gene Expression. Issue 1 (2nd February 2015) - Kadam, Anagha; Janto, Benjamin; Eutsey, Rory; Earl, Joshua P.; Powell, Evan; Dahlgren, Margaret E.; Hu, Fen Z.; Ehrlich, Garth D.; Hiller, N. Luisa
Abstract: There is extensive genomic diversity among Streptococcus pneumoniae isolates. Approximately half of the comprehensive set of genes in the species (the supragenome or pangenome) is present in all the isolates (core set), and the remaining is unevenly distributed among strains (distributed set). The Streptococcus pneumoniae Supragenome Hybridization (SpSGH) array provides coverage for an extensive set of genes and polymorphisms encountered within this species, capturing this genomic diversity. Further, the capture is quantitative. In this manner, the SpSGH array allows for both genomic and transcriptomic analyses of diverse S. pneumoniae isolates on a single platform. In this unit, we present the SpSGH array, and describe in detail its design and implementation for both genomic and transcriptomic analyses. The methodology can be applied to construction and modification of SpSGH array platforms, as well to other bacterial species as long as multiple whole‐genome sequences are available that collectively capture the vast majority of the species supragenome. © 2015 by John Wiley & Sons, Inc.